2008
DOI: 10.1002/cjce.20092
|View full text |Cite
|
Sign up to set email alerts
|

A replicated investigation of nitroxide‐mediated radical polymerization of styrene over a range of reaction conditions

Abstract: A comprehensive experimental investigation of nitroxide-mediated radical polymerization (NMRP) of styrene using 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) as controller is presented. Polymerizations with a bimolecular initiator (benzoyl peroxide; BPO) were carried out at 120 and 130 • C, with TEMPO/BPO molar ratios ranging from 0.9 to 1.5. Results indicate that increasing temperature increases the rate of polymerization while the decrease in molecular weights is only slight. It was also observed that increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 41 publications
2
32
0
1
Order By: Relevance
“…4b). Nabifar et al 20 reported similar results for the living free radical polymerization of styrene using BPO as the initiator and considering tempera- tures of 120 and 130…”
Section: Effect Of Temperature Using Tbec As Initiatorsupporting
confidence: 68%
See 2 more Smart Citations
“…4b). Nabifar et al 20 reported similar results for the living free radical polymerization of styrene using BPO as the initiator and considering tempera- tures of 120 and 130…”
Section: Effect Of Temperature Using Tbec As Initiatorsupporting
confidence: 68%
“…2b that the profiles considering different molar ratios of TEMPO and TBEC are very similar. Nabifar et al 20 also related that the effect of this factor on molecular weights was not pronounced for some experimental conditions. Figure 2b also shows that the molecular weights increase linearly with conversion, which is expected for a controlled polymerization process.…”
Section: Effect Of the Molar Ratio [Tempo]/[tbec]mentioning
confidence: 92%
See 1 more Smart Citation
“…We are not offering a literature (or background) review on NMRP, as the emphasis here is to demonstrate the benefits of specific aspects of the Bayesian design of experiments and not the kinetics of NMRP. For the interested reader, kinetic and modeling information closely related to the case study presented herein could be found in references [5][6][7]. The case study that follows implements the Bayesian design steps of Table 3, with added emphasis on the interpretation of diagnostic criteria and information measures.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular weight is selected to be measured at 50 % conversion, first of all because 50 % is the mid-point of the process, so the molecular weight behavior is well established by then. In addition, prior experimental information [13,14] advises that molecular weight measurements show more scatter at higher conversion levels (80-95 %) for NMRP of styrene. Replicates of molecular weight measurements available from prior experimental work can give a good idea about the expected variability in the response.…”
Section: Case Study 1: N-trials Experiments Vs Sequences Of Fewer Trialsmentioning
confidence: 99%